Effect of sintering and boron content on rare earth dopant distribution in long afterglow strontium aluminate. Issue 12 (September 2020) - Khabbaz Abkenar, Sirous; Kocjan, Andraž; Samardžija, Zoran; Fanetti, Mattia; Coşgun Ergene, Arzu; Šturm, Sašo; Sezen, Meltem; Ow-Yang, Cleva W.
Highlights: B2 O3 in Pechini-processed strontium aluminate tunes rare earth dopant partitioning. SPS freezes in Eu 2+, Dy 3+ and B concentrations above solubility limits of Sr4 Al14 O25. When diffusion is limited, Eu Dy concentration exceed solubility limits and segregate to the intergranular phase. Crystal structure of grains identified by Eu 2+ peaks in SEM cathodoluminescence spectra. 4-fold coordinated B appears in Sr4 Al14 O25 grains exhibiting persistent afterglow. Abstract: B has been proposed to extend persistent luminescence from minutes to > 10 h in Eu, Dy, and B co-doped Sr4 Al14 O25 (S4A7EDB) by facilitating the incorporation of Eu 2+ and Dy 3+ into adjacent Sr sub-lattice sites and enabling energy transfer between them. To evaluate additional influences of B on the kinetics of microstructural evolution and dopant distribution that support afterglow in S4A7EDB, the effect of heating rates to 1300 °C is compared for spark-plasma sintering and conventional sintering, with and without the addition of B2 O3 . Analysis of the microstructure and elemental distribution, by a combination of imaging, WDS, and CL in the SEM, XRD, dilatometry, and STEM-EELS, reveals that when the diffusivity of Eu and Dy is increased, Eu and Dy segregate to the intergranular phase. The partitioning of Eu and Dy concentrations to below their solubility limit in the grains appears to be essential to material structure enabling longer afterglow.